CONCEPTUAL SKILLS IN PERSONS WITH VISUAL IMPAIRMENT - Anđelković, Marija (Specijalna edukacija i rehabilitacija, 2017)
Conceptual skills enable the development of abilities necessary for controlling certain aspects of life. They include communication skills, functional literacy, and self-direction skills. The aim of this paper was to determine the acquisition of conceptual skills in persons with visual impairment. The research was conducted on a sample of 127 persons with visual impairment, 19-60 years of age. Conceptual Skills Domain of Adaptive Behavior Assessment System II (ABAS-II) was used to obtain data on the acquisition of conceptual skills. It was determined that age (p=0.001) and the category of visual impairment (blindness and low vision) (p=0.000) were significant factors for the acquisition of conceptual skills in persons with visual impairment. On the other hand, time when vision loss occurred was not a significant factor for acquiring conceptual skills in persons with visual impairment (p=0.195).
Keywords: self-direction skills; functional literacy; communication skills; conceptual skills; visual impairment